Social Network Theory in Advertisers' Development to Increase Luxury Goods Purchases - Hamami, Finka; Masnita, Yolanda; Madliyas, Madliyas (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
The influence of advertising attitude as a mediator in the relationship between advertisers and purchasing intention. This research also aims to see the influence of friends and peers and celebrities on purchasing intention. The sample in this study was 113 respondents with the criteria of having purchased luxury goods. To obtain a sample, this research uses a non-probability sampling technique. Using a structural equation model (PLS), this research shows that advertising attitude can mediate the positive influence of advertisers on purchasing intention. also shows that friends and peers and celebrities have a positive influence on purchasing intention. From the results of research that has been conducted, it shows that advertising attitude mediates the positive influence of advertisers on purchasing intention. The results of this research show that friends and peers have a positive influence on purchasing intention. The research results also show that celebrities have a positive effect on purchasing intention. In this research, social network theory provides an understanding that the development of social media which aims to become a link between individuals has an impact on purchasing behavior, especially online purchases. This research contributes to new literature in the field of marketing management related to advertisers, advertising attitudes, friends and peers, celebrities and purchasing intention. For further research, other variables can be used that might influence purchasing intention other than the variables used in this research.